Hitchhiking Trypanosoma cruzi minicircle DNA affects gene expression in human host cells via LINE-1 retrotransposon - Barbosa, Augusto Mello Simões (2006)
The horizontal transfer of Trypanosoma cruzi mitochondrial minicircle DNA to the genomes of naturally infected humans may play an important role in the pathogenesis of Chagas disease. Minicircle integrations within LINE-1 elements create the potential for foreign DNA mobility within the host genome via the machinery associated with this retrotransposon. Here we document integration of minicircle DNA fragments in clonal human macrophage cell lines and their mobilization over time. The movement of an integration event in a clonal transfected cell line was tracked at three months and three years post-infection. The minicircle sequence integrated into a LINE-1 retrotransposon; one such foreign fragment subsequently relocated to another genomic location in association with associated LINE-1 elements. The p15 locus was altered at three years as a direct effect of minicircle/LINE-1 acquisition, resulting in elimination of p15 mRNA. Here we show for the first time a molecular pathology stemming from mobilization of a kDNA/LINE-1 mutation. These genomic changes and detected transcript variations are consistent with our hypothesis that minicircle integration is a causal component of parasite-independent, autoimmune-driven lesions seen in the heart and other target tissues associated with Chagas disease.